Pengaruh Lokus Kendali, Lingkungan Sosial dan Perilaku Produktif Mahasiswa terhadap Intensi Berwirausaha - Didit Darmawan (Unversitas Muhammadiyah Mataram, 2022)
Abstract: Entrepreneurship is a concept of independence that must be learned by students as educated human resources. Entrepreneurship is one of the solutions to achieve a level of welfare in the future apart from working as an employee in a company. With various dynamics in the academic environment at universities, it can support the formation of an entrepreneurial spirit among students. Entrepreneurial intentions are important to observe as a basis for entrepreneurial behavior and solutions for unemployment among graduates. This study intends to study and determine the role of locus of control, social environment, and productive behavior in shaping entrepreneurial intentions. The study involved 100 respondents taken from several universities in Surabaya. With the regression technique known several findings. The locus of control is proven to have a real role in shaping students' intentions to become entrepreneurs. The social environment supports students to be interested in entrepreneurship. Productive behavior needs to be made stronger because it is one of the determinants of entrepreneurial intentions.Abstrak: Kewirausahaan adalah konsep kemandirian yang harus dipelajari oleh mahasiswa sebagai sumber daya manusia terpelajar. Kewirausahaan adalah salah satu solusi mencapai tingkat kesejahteraan di masa depan selain bekerja sebagai pekerja di perusahaan. Dengan berbagai dinamika di lingkungan akademis di perguruan tinggi dapat menunjang keterbentukan jiwa kewirausahaan di kalangan mahasiswa. Intensi berwirausaha penting untuk diamati sebagai dasar perilaku kewirausahaan dan solusi bagi pengangguran di kalangan sarjana. Studi ini bertujuan untuk mempelajari dan mengetahui peran dari lokus kendali, lingkungan sosial, dan perilaku produktif terhadap intensi berwirausaha. Studi melibatkan 100 responden yang diambil dari beberapa perguruan tinggi di Surabaya. Dengan teknik regresi diketahui beberapa temuan. Lokus kendali terbukti memiliki peran nyata membentuk intensi mahasiswa untuk berwirausaha. Lingkungan sosial mendukung mahasiswa untuk berminat berwirausaha. Perilaku produktif perlu dibentuk lebih kuat karena merupakan salah satu determinan dari intensi berwirausaha.